2011
DOI: 10.1016/b978-0-12-385897-9.00002-1
|View full text |Cite
|
Sign up to set email alerts
|

Malaria Distribution, Prevalence, Drug Resistance and Control in Indonesia

Abstract: Approximately 230 million people live in Indonesia. The country is also home to over 20 anopheline vectors of malaria which transmit all four of the species of Plasmodium that routinely infect humans. A complex mosaic of risk of infection across this 5000-km-long archipelago of thousands of islands and distinctive habitats seriously challenges efforts to control malaria. Social, economic and political dimensions contribute to these complexities. This chapter examines malaria and its control in Indonesia, from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
166
0
15

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 142 publications
(182 citation statements)
references
References 135 publications
(289 reference statements)
1
166
0
15
Order By: Relevance
“…This setting is typical for many rural malaria-endemic areas in Indonesia, particularly high risk coastal zones. 19 Residents of the study village work principally in agriculture, have no public electricity or water, and reside overwhelmingly in traditional large thatch and bamboo homes averaging 80 m 3 that offer little protection from mosquito entry. Thus, the site maintained relatively high malaria attack rates, primarily from An.…”
Section: Methodsmentioning
confidence: 99%
“…This setting is typical for many rural malaria-endemic areas in Indonesia, particularly high risk coastal zones. 19 Residents of the study village work principally in agriculture, have no public electricity or water, and reside overwhelmingly in traditional large thatch and bamboo homes averaging 80 m 3 that offer little protection from mosquito entry. Thus, the site maintained relatively high malaria attack rates, primarily from An.…”
Section: Methodsmentioning
confidence: 99%
“…According to surveys conducted between 1900 and 2008 in 2,366 locations in Indonesia, four species of Plasmodium may infect humans, P. falciparum, P. vivax, P. malariae and P. ovale. P. falciparum is the most common parasite that is contagious in Indonesia, with prevalence rates of 33% in Papua, 29% in Lesser Sundas and 21% in Sumatra (2). Findings of studies performed in other parts of Indonesia, including the Thousand Island district (3), Nias Island (4), Sumba Island (5) and Aceh (6), have shown that P. falciparum was the most frequent parasite that caused malaria.…”
Section: Introductionmentioning
confidence: 99%
“…Plasmodium falciparum (PF), a microorganism that belongs to the phylum Apicomplexa [1], is the most common cause of malaria in Indonesia [2]. The first-line treatment for uncomplicated PF malaria in the country is the artesunate-amodiaquine combination [2].…”
Section: Introductionmentioning
confidence: 99%
“…The first-line treatment for uncomplicated PF malaria in the country is the artesunate-amodiaquine combination [2]. However, a failure rate of more than 10%, associated with drug resistance, was reported for this treatment in Indonesia for the period 2000-2007 [2].…”
Section: Introductionmentioning
confidence: 99%